{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Section 3.6-solutions-2 - to(aqt73 Section 3.6...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
to (aqt73) – Section 3.6 – isaacson – (55826) 1 This print-out should have 6 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0points Find y when xy + 3 x + 4 x 2 = 5 . 1. y = y + 3 + 8 x x 2. y = y + 3 + 4 x x 3. y = - y + 3 + 8 x x correct 4. y = - ( y + 3 + 8 x ) 5. y = 3 + 4 x - y x 6. y = - y + 3 + 4 x x Explanation: Differentiating implicitly with respect to x we see that d dx ( xy + 3 x + 4 x 2 ) = d dx (5) . Thus ( xy + y ) + 3 + 8 x = 0 , and so xy = - y - 3 - 8 x . Consequently, y = - y + 3 + 8 x x . 002 10.0points If y = y ( x ) is defined implicitly by y 2 + xy + 4 = 0 , find the value of dy/dx at the point (5 , - 1). 1. dy dx vextendsingle vextendsingle vextendsingle (5 , 1) = - 1 3 2. dy dx vextendsingle vextendsingle vextendsingle (5 , 1) = 1 3 correct 3. dy dx vextendsingle vextendsingle vextendsingle (5 , 1) = - 2 3 4. dy dx vextendsingle vextendsingle vextendsingle (5 , 1) = - 1 5. dy dx vextendsingle vextendsingle vextendsingle (5 , 1) = 1 6.
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}